Prevalence of brucellosis in Pakistan with reference to South Asia and Middle East: A comparative review - Ahmad, M; Akhtar, R; Altaf, I; Bhutta, ZA; Farhab, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Brucellosis is a well-known zoonotic disease that causes serious health-related issues both in the humans and livestock population of the world. The prevalence of this disease has been increased significantly especially in developing and under-developed countries for the last few decades because of religious, socioeconomic, political and sanitary concerns. Lack of resources, local awareness, sufficient laboratory support, effective control strategies, and proper vaccination programs are yet other factors contributing to the spread of this disease. Because of high zoonotic potential Brucella species pose a significant threat to the human population involved in handling, rearing, and consumption of contaminated dairy products. The economy of many countries in the world mostly depends upon the rearing of the healthy and high-yielding livestock population. This disease causes notable economic losses in terms of low production, abortion followed by low fertility and repeat breeding. This review includes generalizing information regarding economic losses and public health issues caused by brucellosis in different countries of the world.